Warming effects on permafrost ecosystem carbon fluxes associated with plant nutrients - Fei Li; Yunfeng Peng; Susan M. Natali; Kelong Chen; Tianfeng Han; Guibiao Yang; Jinzhi Ding; Dianye Zhang; Guanqin Wang; Jun Wang; Jianchun Yu; Futing Liu; et al. (Ecology, 2017)
Large uncertainties exist in carbon (C)‐climate feedback in permafrost regions, partly due to an insufficient understanding of warming effects on nutrient availabilities and their subsequent impacts on vegetation C sequestration. Although a warming climate may promote a substantial release of soil C to the atmosphere, a warming‐induced increase in soil nutrient availability may enhance plant productivity, thus offsetting C loss from microbial respiration. Here, we present evidence that the positive temperature effect on carbon dioxide ( CO 2 ) fluxes may be weakened by reduced plant nitrogen (N) and phosphorous (P) concentrations in a Tibetan permafrost ecosystem. Although experimental warming initially enhanced ecosystem CO 2 uptake, the increased rate disappeared after the period of peak plant growth during the early growing season, even though soil moisture was not a limiting factor in this swamp meadow ecosystem. We observed that warming did not significantly affect soil extractable N or P during the period of peak growth, but decreased both N and P concentrations in the leaves of dominant plant species, likely caused by accelerated plant senescence in the warmed plots. The attenuated warming effect on CO 2 assimilation during the late growing season was associated with lowered leaf N and P concentrations. These findings suggest that warming‐mediated nutrient changes may not always benefit ecosystem C uptake in permafrost regions, making our ability to predict the C balance in these warming‐sensitive ecosystems more challenging than previously thought.